Sperm motility parameters for Steindachneridion parahybae based on open-source software - Sanches, E. A. [UNESP]; Marcos, R. M.; Okawara, R. Y.; Caneppele, D.; Bombardelli, R. A.; Romagosa, E. (Hindawi, 2013)
Summary: The objective of this work was to evaluate the sperm motility of 13 Steindachneridion parahybae males using open-source software (ImageJ/CASA plugin). The sperm activation procedure and image capture were initiated after semen collection. Four experimental phases were defined from the videos captured of each male as follows: (i) standardization of a dialogue box generated by the CASA plugin within ImageJ; (ii) frame numbers used to perform the analysis; (iii) post-activation motility between 10 and 20 s with analysis at each 1 s; and (iv) post-activation motility between 10 and 50 s with analysis at each 10 s. The settings used in the CASA dialogue box were satisfactory, and the results were consistent. These analyses should be performed using 50 frames immediately after sperm activation because spermatozoa quickly lose their vigor. At 10 s post-activation, 89.1% motile sperm was observed with 107.2 μm s-1 curvilinear velocity, 83.6 μm s-1 average path velocity, 77.1 μm s-1 straight line velocity; 91.6% were of straightness and 77.1% of wobble. The CASA plugin within ImageJ can be applied in sperm analysis of the study species by using the established settings. © 2013 Blackwell Verlag GmbH.